Compositionally Graded Microstructure for Ag-Fe Nanoparticles - Srivastava, Chandan; Sushma, K. V. L. (Nano-Micro Letters, 2012)
Ag-Fe nanoparticles with a highly Ag rich average composition were synthesized by the sonochemical route. Silver-iron system exhibits a wide miscibility gap in the bulk materials. Interestingly, a graded compositional profile along the nanoparticle radius was observed. Regions at and near the surface of the nanoparticle contained both Ag and Fe atoms. The composition got relatively deficient Fe towards the center of the particle with particle core made up of pure Ag. Alloying of Ag and Fe is confirmed by the absence of diffraction signal corresponding to pure Fe phase and presence of a paramagnetic phase in nanoparticles containing a diamagnetic (Ag) and ferromagnetic (Fe) elements.